2018
DOI: 10.1186/s12875-018-0780-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with primary healthcare services: are there any links with patients’ symptoms of anxiety and depression?

Abstract: BackgroundThe aim of our study was to determine the association of anxiety and depression symptoms, as well as the main socio-demographic factors, with patients’ satisfaction with primary healthcare services.MethodsThe respondents were asked to fill out an anonymous questionnaire that included information on the patients’ gender, age, place of residence, education, ethnicity, the type of clinic they visited and the presence of chronic diseases. Patient satisfaction was evaluated by using a short version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
(27 reference statements)
0
29
0
3
Order By: Relevance
“…Although depressed or anxious patients tend to be less satisfied with their primary care services, trust in healthcare providers, as an attribute of patient satisfaction with healthcare providers, has not been adequately investigated [22]. Moreover, though small to moderate correlations have been found in studies that examined the relationship between patient trust in healthcare providers and different health outcomes, there is evidence of an upward bias in many of these studies [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although depressed or anxious patients tend to be less satisfied with their primary care services, trust in healthcare providers, as an attribute of patient satisfaction with healthcare providers, has not been adequately investigated [22]. Moreover, though small to moderate correlations have been found in studies that examined the relationship between patient trust in healthcare providers and different health outcomes, there is evidence of an upward bias in many of these studies [23].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction of patients with health care has been described as the degree to which a patient's desired expectations, goals and or preferences are met by the health care provider and or service [16]. Some studies [17,18] have shown that patients are more likely to take appropriate preventive measures and adhere to their treatment plan if they were satis ed with level of care they were offered. The ndings from our study showed varying level of satisfaction for some of the items on the PSQ-18 and to each of the seven sub scales of the tool by study respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction of patients with health care has been described as the degree to which a patient's desired expectations, goals and or preferences are met by the health care provider and or service [21]. Some studies [22,23] have shown that patients are more likely to take appropriate preventive measures and adhere to their treatment plan if they were satis ed with level of care they were offered. The need for health systems to effectively deliver various dimensions of care, including patient-centred care is becoming ever more recognized that high-quality medical care, in addition to improved coverage of maternal and child health services, is essential to achieving the Sustainability Goal's goal of reducing maternal and child mortality [24][25][26].…”
Section: Discussionmentioning
confidence: 99%